2016
DOI: 10.5603/fm.a2015.0128
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between selected parameters of nasal cavity in neonates and young infants — computed tomography study

Abstract: Background: Correlations between selected metric parameters of the nasal cavity and nasopharynx in children without atresia may be useful for anticipating probable dimensions of this region in living subjects (Folia Morphol 2016; 75, 3: 334-340)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…On the other hand, many viruses preferentially, or exclusively replicate in dividing cells; hence, their components are potentially becoming an important source/inspiration in the search of drugs that preferentially target cancer stem cells ( Akbari-Birgani et al, 2016 ; Farahani et al, 2014 ; Jain et al, 2015 ; Jain et al, 2016 ). Beside viral methods, some clinically tested drugs as well as new drugs with preferential toxicity towards cancer stem cells are increasingly becoming available ( Jangamreddy et al, 2013 ; Likus et al, 2016a ; Likus et al, 2016b ; Moghadam et al, 2015 ; Moosavi et al, 2016 ). Such tasks are facilitated by recent progress in methodologies that allows for better detection and monitoring of cancer stem cells ( Cieslar-Pobuda et al, 2016 ; Cieslar-Pobuda et al, 2015 ; Likus et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many viruses preferentially, or exclusively replicate in dividing cells; hence, their components are potentially becoming an important source/inspiration in the search of drugs that preferentially target cancer stem cells ( Akbari-Birgani et al, 2016 ; Farahani et al, 2014 ; Jain et al, 2015 ; Jain et al, 2016 ). Beside viral methods, some clinically tested drugs as well as new drugs with preferential toxicity towards cancer stem cells are increasingly becoming available ( Jangamreddy et al, 2013 ; Likus et al, 2016a ; Likus et al, 2016b ; Moghadam et al, 2015 ; Moosavi et al, 2016 ). Such tasks are facilitated by recent progress in methodologies that allows for better detection and monitoring of cancer stem cells ( Cieslar-Pobuda et al, 2016 ; Cieslar-Pobuda et al, 2015 ; Likus et al, 2016b ).…”
Section: Discussionmentioning
confidence: 99%
“…This may impact the ease of maneuverability of instrumentation within the sinonasal cavity and necessitate the use of smaller equipment. The published norms for piriform aperture width at birth, 2 years, and 5 years reveal increasing diameter from 15 to 18 mm to greater than 20 mm, respectively . Prior radioanatomic studies revealed no statistically significant increase in piriform aperture diameter from that of the neonate until 15 to 18 years, but the clinical significance of these small changes is notable.…”
Section: Introductionmentioning
confidence: 88%
“…The pyriform aperture poses the second restriction point for skull base surgeons. Previous radioanatomic studies report a mean pyriform aperture diameter of 15 mm at birth, gradually increasing to 18 mm by age 2 years and exceeding 20 mm by age 5 years [5][6][7]. While these measurements may seem trivial, their clinical significance lies in the nearly doubled cross-sectional area of the aperture, transitioning from 15 mm to 20 mm in diameter [8].…”
Section: Nasal and Pyriform Aperturesmentioning
confidence: 96%